The Associations of Clean and Healthy Behavior, Social Capital, and Nutritional Status in Children Under Five in Waingapu Health Center - Stevani Rambu Kudu; Yulia Lanti Retno Dewi; Setyo Sri Raharjo (Masters Program in Public Health, Sebelas Maret University, 2021)
Background: Quality nutrition is a determinant of children's survival, health, and growth. Nutritional problems and lack of nutrient intake are also about whether bad in the environment or commonly known as clean and healthy behavior. Social capital refers to social relationships and connections between individuals because it is more of a relationship between individuals than an individual attribute. This study aimed to examine the relationship between clean and healthy behavior and social capital with the nutritional status of children under five at the Waingapu City Health Center.Subjects and Method: This was a cross-sectional study conducted at the Waingapu Health Center, East Sumba, East Nusa Teng-gara, Indonesia, in April 2021. The sample was 200 mothers, and children under five were selected randomly. The dependent variable was child nutritional status (WAZ). The independent variables were social capital, clean and healthy behavior, gender, maternal age, mater-nal occupation, and maternal education. Data were collected by using a questionnaire and analyzed by multiple logistic regression.Results: Clean and healthy lifestyle improved good nutritional status (OR= 5.50; 95% CI= 1.19 to 25.43; p= 0.029). High social capital increased good nutritional status (OR= 2.28; 95% CI= 1.15 to 4.51; p= 0.017).Conclusion: Healthy, clean living behavior, and high social capital improve good nutriational status.Keywords: clean and healthy behavior, social capital, nutritional statusCorrespondence: Stevani Rambu Kudu. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: Stevanir09@student.uns.ac.id. Mobile: 082226431161.Journal of Health Promotion and Behavior (2021), 06(01): 57-66https://doi.org/10.26911/thejhpb.2021.06.01.06